2020
DOI: 10.1016/j.tetlet.2019.151473
|View full text |Cite
|
Sign up to set email alerts
|

First total syntheses of the pro-resolving lipid mediators 7(S),13(R),20(S)-Resolvin T1 and 7(S),13(R)-Resolvin T4

Abstract: The first total syntheses of the pro-resolving lipid mediators 7(S),13(R),20(S)-Resolvin T1 [7(S),13(R),20(S)-RvT1] and 7(S),13(R)-Resolvin T4 [7(S),13(R)-RvT4], derived from n-3 docosapentaenoic acid (n-3 DPA), are described. 7(S),13(R),20(S)-RvT1 was prepared from 7(S),13(R)-RvT4 via an enzymatic lipoxidase reaction. 7(S),13(R)-RvT4 was obtained by total synthesis where the chiral centers at C7 and C13 where introduced by a Noyori transfer hydrogenation and a chiral pool strategy respectively. Wittig reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…16 The 1 H and 13 C NMR spectral data for 4 were in good agreement with the reported data for resolving T4. 7 In summary, we have achieved a total synthesis of resolvin T4 (4) through a sequential Wittig reaction between intermediates 5, 8, and 9. Enal 5 was derived from alkynol (S)-7 in 16 steps.…”
Section: Scheme 1 Synthetic Plan For Resolvin T4 (4)mentioning
confidence: 97%
See 1 more Smart Citation
“…16 The 1 H and 13 C NMR spectral data for 4 were in good agreement with the reported data for resolving T4. 7 In summary, we have achieved a total synthesis of resolvin T4 (4) through a sequential Wittig reaction between intermediates 5, 8, and 9. Enal 5 was derived from alkynol (S)-7 in 16 steps.…”
Section: Scheme 1 Synthetic Plan For Resolvin T4 (4)mentioning
confidence: 97%
“…In 2020, Spur et al reported the first total synthesis of resolvin T4. 7 In their synthesis, the hydroxy moiety in the C10-C22 alkyne was derived from an optically active glycidol derivative. To develop another synthetic method for resolvin T4 with flexibility for the synthesis of its analogues, we investigated a new method that does not rely on a chiral pool in constructing the hydroxy carbons.…”
mentioning
confidence: 99%
“…The biosynthesis of RvTs occur via neutrophil-endothelial interactions, where the precursor n-3 docosapentaenoic acid (n-3 DPA) is converted to 13-hydro(peroxy)-7Z,10Z,13,14E,16Z,19Z docosapentaenoic acid by endothelial COX-2, which is then acted upon by COX-2 mediated peroxidase and converted to 13(R)-hydroxy-7Z,10Z,13R,14E,16Z,19Z docosa- pentaenoic acid [125] , [126] . This intermediate is then converted to 7-hydroperoxy-13(R)-hydroxy-docosapentaenoic acid, which after reduction of the hydroperoxy-group gives RvT4, later the action of enzymatic lipoxidase converts RvT4 to RvT1 [124] . It is also known that the 7-hydroperoxy-13(R)-hydroxy-docosapentaenoic acid forms an allylic epoxide intermediate [7,8-epoxy], that is hydrolyzed to RvT2 and RvT3.Rodriguez and spur synthesized RvT2 and its 13(R)-epimer for the first time, they showed that enzymatic lipoxidase introduces hydroxyl groups at C-7 and C-20 with (S)-chirality in PUFAs [127] .Evidence shows that biosynthesis of RvTs can be triggered by atorvastation, through S-nitrosylation of COX-2 [125] .…”
Section: Specialized Pro‑resolving Lipid Mediators (Spms)mentioning
confidence: 99%
“…These new findings ( Table 1 ) and many other human studies for SPMs from international experts [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] would not have been possible without the i) complete stereochemical assignments of each of the potent bioactive SPMs produced by human and mouse leukocytes, ii) their biosynthesis from n-3 essential fatty acids (EPA and DHA) and iii) total organic synthesis with rigorous matching studies with endogenous SPMs along with our dedicated and talented organic chemistry collaborators summarized herein. In this relatively new SPM field, the Serhan lab has collaborated for many years with Professor Nicos Petasis and colleagues as part of the total synthesis core of our NIH-supported Program Project grant P01GM095467, Professor Trond Hansen and team in Oslo, Norway [ 56 ], Professor Bernd Spur and Anna Rodriguez [ [57] , [58] , [59] ], and the organic synthesis group at Cayman Chemical; for examples, see the custom synthesis of benzo-RvD1 analog mimetic [ 60 ] and the new RvE4 [ 61 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiesmentioning
confidence: 99%